The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Multi-Omics Characterization of a KIF1C Structural Variant in a Patient with a Complex Movement Disorder Partially Responsive to Deep Brain Stimulation - Mirja Thomsen; Max Borsche; Vicente A. Yépez; Dirk Rasche; Kristian K. Ullrich; Vera Tadic; Saad M. Abdelwakeel; Hauke Busch; Sören Franzenburg; Joanne Trinh; Christine Klein; Katja Lohmann; et al. (The Cerebellum, 2026)
Biallelic KIF1C variants are associated with a spectrum of neurological phenotypes, including spasticity, cerebellar ataxia, chorea, and dystonia. Most reported patients involve single-nucleotide variants, whereas copy number variants (CNVs) have been described only once in the PubMed-listed literature. The therapeutic potential of deep-brain stimulation (DBS) in KIF1C -related disease has not yet been evaluated. We report a patient presenting with spasticity, ataxia, dystonia, and head tremor, in whom prior exome sequencing was inconclusive. A multi-omics approach was applied, including optical genome mapping (OGM), genome sequencing, and transcriptome sequencing. The clinical effect of DBS was assessed. OGM revealed a homozygous KIF1C Exon 17–18 deletion, retrospectively detectable in exome and genome data but initially missed by sequence analysis. Transcriptome sequencing demonstrated significantly reduced KIF1C expression and absence of normally spliced transcripts around those exons, consistent with a loss-of-function mechanism. DBS led to partial clinical improvement, with notable reduction of dystonia and head tremor. Structural variants may be an underrecognized cause of complex movement disorders involving spasticity, ataxia, and dystonia. Diagnostic methods specifically targeting structural variation, such as OGM or CNV analysis of short-read data, can be essential for diagnosis. Transcriptome data add valuable functional insight. This report also suggests that DBS may offer symptomatic benefit in KIF1C -associated disease, particularly for dystonic signs.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Analysis and Comparison of Natural Shear and Induced Tensile Fractures for Caprock Leakage Assessment - Sahyuo Achuo Dze; Tomos Phillips; Reza Najafi-Silab; Sarah Perez; Tom Bultreys; Vladimir Novak; Christian M. Schlepütz; Veerle Cnudde; Florian Doster; Kamaljit Singh; Kevin Bisdom; Andreas Busch (Transport in Porous Media, 2026)
The comparison between laboratory-induced and subsurface fractures, and their corresponding flow is still unclear. Here, we examine three natural shear fractures and two induced tensile fractures from the same low-permeability lithology. Using high-resolution synchrotron imaging, we extracted three-dimensional fracture void geometries to analyse aperture distributions, surface roughness, and spatial correlation patterns. We then compared measured fracture transmissivities against theoretical predictions from parallel-plate models (cubic law) and direct numerical simulations (DNS) of flow to evaluate consistency and uncertainties. We find that despite differences in heterogeneity, induced tensile and natural shear fractures can generally yield similar flow in caprocks. Our comparisons further indicate that the choice of flow estimation method can introduce more uncertainty than the fracture opening mode.

Management practices and soil health: Insights from dairy farms in the United States - Che-Jen Hsiao; Mara Cloutier; Daniel Liptzin; Nathaniel Looker; Christine Molling; Michael Cope; Randall D. Jackson; Gregg R. Sanford; Matthew D. Ruark; Dennis Busch; Karl Czymmek; Quirine M. Ketterings; et al. (Agriculture, Ecosystems & Environment, 2026)

How mixed messages may be better than avoidance in climate change education - Kathryn Stevenson; K. C. Busch; M. Nils Peterson; Danielle A. Frank; Regina Ayala Chavez (Journal of Environmental Studies and Sciences, 2025)

OS01-11 Development of a Human Intestinal Stem Cell-Derived 2D Monolayer Model for Transport and Metabolism Studies - J. Wang; T. Walraven; M. Busch; H. Bouwmeester; N. Kramer (Toxicology Letters, 2025)

Oral inflammatory myofibroblastic tumour in a dog - S. Muller; M. Croci; I. Porcellato; P. Slootweg; M. Busch (Journal of Comparative Pathology, 2025)

Economic and environmental performance of biomass gasification for renewable natural gas production in the context of the U.S. natural gas supply - O.A. Oyedeji; A.M. Moore; D. Kamath; I.K. Busch; S.J. Curran; M. Henriksen; M. Jamieson; T.E. Fout; E.G. Webb; M.H. Langholtz; T.J. Theiss (Biomass and Bioenergy, 2025)

Population genetic structure in two contrasting human-altered environments of yellow pygmy rice rat Oligoryzomys flavescens - E. Muschetto; I. E. Gómez Villafañe; M. Scaltritti; J. Fraschina; V. León; L. Adduci; D. Hancke; S. Guidobono; G. R. Cueto; M. A. Tripodi; E. Hasson; M. Busch; et al. (Oecologia, 2025)

The penetration efficiency of a dissolved model drug into hair follicles depends on the concentration of added nanoparticles - Loris Busch; Darya Asadzadeh; Anna Lena Klein; Phuvamin Suriyaamporn; Mont Kumpugdee Vollrath; Cornelia M. Keck; Martina C. Meinke (Drug Delivery and Translational Research, 2025)
Hair follicles have recently emerged as promising drug delivery targets and gates for skin penetration. The so-called ratchet effect, which is based on an interaction between the hair shaft surface, the intrafollicular stratum corneum and nanoparticles, has proven to be very effective for the transport of active ingredients. Especially the nanoparticle-assisted decolonization of hair follicles constitutes an interesting new area of application. In a recently published work it was shown that small molecules as well as macromolecules solved in an outer phase of a formulation can be transported into the deeper parts of the hair follicles by adding nanoparticles to the formulation. In this case the nanoparticles constitute an entity independent of the drug and the transport is hypothesized to be based on an adhesion effect. In the present work, we focused on the impact of the particle concentration in the formulation on the transport efficiency of the model drug fluorescein sodium into hair follicles utilizing an ex vivo porcine skin model. It was observed that a particle concentration of 4% significantly enhances the transport efficiency of fluorescein as compared to 2% particle concentration. Doubling the concentration to 8% did not significantly increase the penetration depth. The effect evolved more efficiently when using 4 Hz circular motion massage as compared to 100 Hz oscillating massage. These results deliver interesting information on the optimal formulation as well as application parameters for a future application in clinical studies for e.g. skin antisepsis purposes. Graphical abstract

Semi-structured citizen science data reveal mixed effectiveness of EU Special Protection Areas (SPA) in Germany - F.J. Pflüger; C. Frank; M. Busch; J. Wahl; R. Dröschmeister; C. Sudfeldt; J. Kamp (Biological Conservation, 2024)

Elevated risk of adverse effects from foodborne contaminants and drugs in inflammatory bowel disease: a review - Tom Walraven; Mathias Busch; Jingxuan Wang; Joanne M. Donkers; Marjolijn Duijvestein; Evita van de Steeg; Nynke I. Kramer; Hans Bouwmeester (Archives of Toxicology, 2024)
The global burden of Inflammatory bowel disease (IBD) has been rising over the last decades. IBD is an intestinal disorder with a complex and largely unknown etiology. The disease is characterized by a chronically inflamed gastrointestinal tract, with intermittent phases of exacerbation and remission. This compromised intestinal barrier can contribute to, enhance, or even enable the toxicity of drugs, food-borne chemicals and particulate matter. This review discusses whether the rising prevalence of IBD in our society warrants the consideration of IBD patients as a specific population group in toxicological safety assessment. Various in vivo, ex vivo and in vitro models are discussed that can simulate hallmarks of IBD and may be used to study the effects of prevalent intestinal inflammation on the hazards of these various toxicants. In conclusion, risk assessments based on healthy individuals may not sufficiently cover IBD patient safety and it is suggested to consider this susceptible subgroup of the population in future toxicological assessments.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Influence of Local Aperture Heterogeneity on Invading Fluid Connectivity During Rough Fracture Drainage - Tomos Phillips; Tom Bultreys; Jeroen Van Stappen; Kamaljit Singh; Sahyuo Achuo Dze; Stefanie Van Offenwert; Ben Callow; Mostafa Borji; Erik Clemens Boersheim; Vladimir Novak; Christian M. Schlepütz; Veerle Cnudde; et al. (Transport in Porous Media, 2024)
Determining the (in)efficiency of wetting phase displacement by an invading non-wetting phase (drainage) in a single fracture is key to modelling upscaled properties such as relative permeability and capillary pressure. These constitutive relationships are fundamental to quantifying the contribution, or lack thereof, of conductive fracture systems to long-term leakage rates. Single-fracture-scale modelling and experimental studies have investigated this process, however, a lack of visualization of drainage in a truly representative sample at sufficient spatial and temporal resolution limits their predictive insights. Here, we used fast synchrotron X-ray tomography to image drainage in a natural geological fracture by capturing consecutive 2.75 μm voxel images with a 1 s scan time. Drainage was conducted under capillary-dominated conditions, where percolation-type patterns are expected. We observe this continuously connected invasion (capillary fingering) only to be valid in local regions with relative roughness, λ b ≤ 0.56. Fractal dimension analysis of these invasion patterns strongly aligns with capillary fingering patterns previously reported in low λ b fractures and porous media. Connected invasion is prevented from being the dominant invasion mechanism globally due to high aperture heterogeneity, where we observe disconnected invasion (snap-off, fragmented clusters) to be pervasive in local regions where λ b ≥ 0.67. Our results indicate that relative roughness has significant control on flow as it influences fluid conductivity and thus provides an important metric to predict invasion dynamics during slow drainage.

Research and educational applications of the Aerojet General Nucleonics 201-M at the University of New Mexico - Rowdy Davis; Christopher M. Perfetti; Robert D. Busch; Larry L. Wetzel; Carl A. Willis (Annals of Nuclear Energy, 2024)

A novel in vitro high-content imaging assay for the prediction of drug-induced lung toxicity - Paul A. Fitzpatrick; Julia Johansson; Gareth Maglennon; Ian Wallace; Ramon Hendrickx; Marianna Stamou; Kinga Balogh Sivars; Susann Busch; Linnea Johansson; Natalie Van Zuydam; Kelley Patten; Per M. Åberg; et al. (Archives of Toxicology, 2024)
The development of inhaled drugs for respiratory diseases is frequently impacted by lung pathology in non-clinical safety studies. To enable design of novel candidate drugs with the right safety profile, predictive in vitro lung toxicity assays are required that can be applied during drug discovery for early hazard identification and mitigation. Here, we describe a novel high-content imaging-based screening assay that allows for quantification of the tight junction protein occludin in A549 cells, as a model for lung epithelial barrier integrity. We assessed a set of compounds with a known lung safety profile, defined by clinical safety or non-clinical in vivo toxicology data, and were able to correctly identify 9 of 10 compounds with a respiratory safety risk and 9 of 9 compounds without a respiratory safety risk (90% sensitivity, 100% specificity). The assay was sensitive at relevant compound concentrations to influence medicinal chemistry optimization programs and, with an accessible cell model in a 96-well plate format, short protocol and application of automated imaging analysis algorithms, this assay can be readily integrated in routine discovery safety screening to identify and mitigate respiratory toxicity early during drug discovery. Interestingly, when we applied physiologically-based pharmacokinetic (PBPK) modelling to predict epithelial lining fluid exposures of the respiratory tract after inhalation, we found a robust correlation between in vitro occludin assay data and lung pathology in vivo, suggesting the assay can inform translational risk assessment for inhaled small molecules.

Global patterns of allochthony in stream–riparian meta‐ecosystems - Daniel C. Allen; James Larson; Christina A. Murphy; Erica A. Garcia; Kurt E. Anderson; Michelle H. Busch; Alba Argerich; Alice M. Belskis; Kierstyn T. Higgins; Brooke E. Penaluna; Veronica Saenz; Jay Jones; et al. (Ecology Letters, 2024)
Ecosystems that are coupled by reciprocal flows of energy and nutrient subsidies can be viewed as a single “meta‐ecosystem.” Despite these connections, the reciprocal flow of subsidies is greatly asymmetrical and seasonally pulsed. Here, we synthesize existing literature on stream–riparian meta‐ecosystems to quantify global patterns of the amount of subsidy consumption by organisms, known as “allochthony.” These resource flows are important since they can comprise a large portion of consumer diets, but can be disrupted by human modification of streams and riparian zones. Despite asymmetrical subsidy flows, we found stream and riparian consumer allochthony to be equivalent. Although both fish and stream invertebrates rely on seasonally pulsed allochthonous resources, we find allochthony varies seasonally only for fish, being nearly three times greater during the summer and fall than during the winter and spring. We also find that consumer allochthony varies with feeding traits for aquatic invertebrates, fish, and terrestrial arthropods, but not for terrestrial vertebrates. Finally, we find that allochthony varies by climate for aquatic invertebrates, being nearly twice as great in arid climates than in tropical climates, but not for fish. These findings are critical to understanding the consequences of global change, as ecosystem connections are being increasingly disrupted.

Development of a source-specific biomass burning emissions inventory for Washington, Oregon, and California - Claire L. Schollaert; Miriam E. Marlier; Tania M. Busch Isaksen (Atmospheric Environment, 2024)

Low rate of detection of SARS-CoV-2 RNA in deceased tissue donors - Melissa A. Greenwald; Eduard Grebe; Valerie Green; Alyce Linthurst Jones; Jeffrey M. Linnen; Phillip Williamson; Michael P. Busch; Matthew J. Kuehnert (Cell and Tissue Banking, 2023)
Given the possibility for disease transmission, this study was performed to determine whether there is detectable SARS-CoV-2 viral RNA in the blood of deceased tissue donors. A retrospective analysis of blood samples from eligible deceased tissue donors from Oct 2019 through June 2020 was performed. Plasma aliquots were initially tested with a SARS-CoV-2 NAT Assay; positive samples were further tested using an alternate NAT and an antibody assay. The proportion of donors with confirmed RNAemia and 95% confidence intervals were computed. Of donor samples collected in 2019, 894 yielded valid results, with 6 initially positive, none of which confirmed positive by alternate NAT. Of donor samples collected in 2020, 2562 yielded valid initial NAT results, with 21 (0.8%) initially positive. Among those, 3 were confirmed by alternate NAT, 17 were not confirmed, and 1 had an invalid alternate NAT result. The rate of SARS-CoV-2 RNAemia in deceased tissue donors is approximately 1 per 1000, and it is unknown whether this RNAemia reflects the presence of infectious virus. Given these results, the risk of transmission through tissue is thought likely to be low.

Evaluation of DNA lesions and radicals generated by a 233 nm far-UVC LED in superficial ex vivo skin wounds - Loris Busch; Marius Kröger; Johannes Schleusener; Anna Lena Klein; Silke B. Lohan; Martin Guttmann; Cornelia M. Keck; Martina C. Meinke (Journal of Photochemistry and Photobiology B: Biology, 2023)

Indicators of water use efficiency across diverse agroecosystems and spatiotemporal scales - David L. Hoover; Lori J. Abendroth; Dawn M. Browning; Amartya Saha; Keirith Snyder; Pradeep Wagle; Lindsey Witthaus; Claire Baffaut; Joel A. Biederman; David D. Bosch; Rosvel Bracho; Dennis Busch; et al. (Science of The Total Environment, 2023)

Interlaboratory comparison of an intestinal triple culture to confirm transferability and reproducibility - Angela A. M. Kämpfer; Ume-Kulsoom Shah; Shui L. Chu; Mathias Busch; Veronika Büttner; Ruiwen He; Barbara Rothen-Rutishauser; Roel P. F. Schins; Gareth J. Jenkins (In vitro models, 2022)
The development and improvement of advanced intestinal in vitro models has received increasing attention in recent years. While the availability of relevant in vitro models is pivotal to advance the replacement and reduction of animal use in research, their robustness is a crucial determinant for intra- and interlaboratory reproducibility. We have developed a standard protocol to build a triple culture model combining two types of human intestinal epithelial cells (Caco-2, HT29-MTX-E12) and macrophages (THP-1), which was tested for transferability and reproducibility between three laboratories. The epithelial tissue barrier development and triple culture stability were investigated as well as the models’ responses to the non-steroidal anti-inflammatory drug diclofenac in terms of barrier integrity, cytotoxicity, and cytokine release. The results of two partner laboratories were compared to previously established benchmark results and quality criteria. For the epithelial co-cultures, the results were overall highly comparable between the laboratories. The addition of THP-1 cells resulted in increased variability and reduced reproducibility. While good correlation was achieved in several endpoints, others showed substantial response differences between the laboratories. Some variations may be addressed with training or demonstrations, whereas others might be related to fundamental differences in the cell lines introduced during routine cell culture and maintenance. Our results underline the importance of interlaboratory transfer studies using standardised experimental procedures, including defined quality criteria and benchmarks, as well as of training when newly establishing complex in vitro models in laboratories.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Evaluation of Cardiotonic Steroid Modulation of Cellular Cholesterol and Phospholipid - Lilian N. D. Silva; Israel J. P. Garcia; Jessica M. M. Valadares; Marco Tulio C. Pessoa; Marina Marques Toledo; Matheus V. Machado; Mileane Souza Busch; Isabella Rocha; José Augusto F. P. Villar; Georgia C. Atella; Herica L. Santos; Vanessa F. Cortes; et al. (The Journal of Membrane Biology, 2021)

Wavelength, dose, skin type and skin model related radical formation in skin - M. C. Meinke; L. Busch; S. B. Lohan (Biophysical Reviews, 2021)
The exposure to sun radiation is indispensable to our health; however, a long-term and high exposure could lead to cell damage, erythema, premature skin aging, and promotion of skin tumors. An underlying pathomechanism is the formation of free radicals which may induce oxidative stress at elevated concentrations. Different skin models, such as porcine-, murine-, human- ex vivo skin, reconstructed human skin (RHS) and human skin in vivo, were investigated during and after irradiation using X- and L-band EPR spectroscopy within different spectral regions (UVC to NIR). The amount of radical formation was quantified with the spin probe PCA and the radical types were measured ex vivo with the spin trap DMPO. The radiation dose influences the types of radicals formed in the skin. While reactive oxygen species (ROS) are always pronounced at low doses, there is an increase in lipid oxygen species (LOS) at high doses. Furthermore, the radical types arise independent from the irradiation wavelength, whereas the general amount of radical formation differs with the irradiation wavelength. Heat pre-stressed porcine skin already starts with higher LOS values. Thus, the radical type ratio might be an indicator of stress and the reversal of ROS/LOS constitutes the point where positive stress turns into negative stress.Compared to light skin types, darker types produce less radicals in the ultraviolet, similar amounts in the visible and higher ones in the infrared spectral region, rendering skin type-specific sun protection a necessity.

DNA ‐stable isotope probing (DNA‐SIP) identifies marine sponge‐associated bacteria actively utilizing dissolved organic matter (DOM) - Sara Campana; Kathrin Busch; Ute Hentschel; Gerard Muyzer; Jasper M. de Goeij (Environmental Microbiology, 2021)
Summary Sponges possess exceptionally diverse associated microbial communities and play a major role in (re)cycling of dissolved organic matter (DOM) in marine ecosystems. Linking sponge‐associated community structure with DOM utilization is essential to understand host–microbe interactions in the uptake, processing, and exchange of resources. We coupled, for the first time, DNA‐stable isotope probing (DNA‐SIP) with 16S rRNA amplicon sequencing in a sponge holobiont to identify which symbiotic bacterial taxa are metabolically active in DOM uptake. Parallel incubation experiments with the sponge Plakortis angulospiculatus were amended with equimolar quantities of unlabelled ( 12 C) and labelled ( 13 C) DOM. Seven bacterial amplicon sequence variants (ASVs), belonging to the phyla PAUC34f, Proteobacteria, Poribacteria, Nitrospirae, and Chloroflexi, were identified as the first active consumers of DOM. Our results support the predictions that PAUC34f, Poribacteria, and Chloroflexi are capable of organic matter degradation through heterotrophic carbon metabolism, while Nitrospirae may have a potential mixotrophic metabolism. We present a new analytical application of DNA‐SIP to detect substrate incorporation into a marine holobiont with a complex associated bacterial community and provide new experimental evidence that links the identity of diverse sponge‐associated bacteria to the consumption of DOM.

Rates of bacterial co-infections and antimicrobial use in COVID-19 patients: a retrospective cohort study in light of antibiotic stewardship - Kathrin Rothe; Susanne Feihl; Jochen Schneider; Fabian Wallnöfer; Milena Wurst; Marina Lukas; Matthias Treiber; Tobias Lahmer; Markus Heim; Michael Dommasch; Birgit Waschulzik; Alexander Zink; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide. Bacterial co-infections are associated with unfavourable outcomes in respiratory viral infections; however, microbiological and antibiotic data related to COVID-19 are sparse. Adequate use of antibiotics in line with antibiotic stewardship (ABS) principles is warranted during the pandemic. We performed a retrospective study of clinical and microbiological characteristics of 140 COVID-19 patients admitted between February and April 2020 to a German University hospital, with a focus on bacterial co-infections and antimicrobial therapy. The final date of follow-up was 6 May 2020. Clinical data of 140 COVID-19 patients were recorded: The median age was 63.5 (range 17–99) years; 64% were males. According to the implemented local ABS guidelines, the most commonly used antibiotic regimen was ampicillin/sulbactam (41.5%) with a median duration of 6 (range 1–13) days. Urinary antigen tests for Legionella pneumophila and Streptococcus peumoniae were negative in all cases. In critically ill patients admitted to intensive care units ( n = 50), co-infections with Enterobacterales (34.0%) and Aspergillus fumigatus (18.0%) were detected. Blood cultures collected at admission showed a diagnostic yield of 4.2%. Bacterial and fungal co-infections are rare in COVID-19 patients and are mainly prevalent in critically ill patients. Further studies are needed to assess the impact of antimicrobial therapy on therapeutic outcome in COVID-19 patients to prevent antimicrobial overuse. ABS guidelines could help in optimising the management of COVID-19. Investigation of microbial patterns of infectious complications in critically ill COVID-19 patients is also required.

A Microbial Nitrogen Engine Modulated by Bacteriosyncytia in Hexactinellid Sponges: Ecological Implications for Deep-Sea Communities - Manuel Maldonado; María López-Acosta; Kathrin Busch; Beate M. Slaby; Kristina Bayer; Lindsay Beazley; Ute Hentschel; Ellen Kenchington; Hans Tore Rapp (Frontiers in Marine Science, 2021)
Hexactinellid sponges are common in the deep sea, but their functional integration into those ecosystems remains poorly understood. The phylogenetically related species Schaudinnia rosea and Vazella pourtalesii were herein incubated for nitrogen and phosphorous, returning markedly different nutrient fluxes. Transmission electron microscopy (TEM) revealed S. rosea to host a low abundance of extracellular microbes, while Vazella pourtalesii showed higher microbial abundance and hosted most microbes within bacteriosyncytia, a novel feature for Hexactinellida. Amplicon sequences of the microbiome corroborated large between-species differences, also between the sponges and the seawater of their habitats. Metagenome-assembled genome of the V. pourtalesii microbiota revealed genes coding for enzymes operating in nitrification, denitrification, dissimilatory nitrate reduction to ammonium, nitrogen fixation, and ammonia/ammonium assimilation. In the nitrification and denitrification pathways some enzymes were missing, but alternative bridging routes allow the microbiota to close a N cycle in the holobiont. Interconnections between aerobic and anaerobic pathways may facilitate the sponges to withstand the low-oxygen conditions of deep-sea habitats. Importantly, various N pathways coupled to generate ammonium, which, through assimilation, fosters the growth of the sponge microbiota. TEM showed that the farmed microbiota is digested by the sponge cells, becoming an internal food source. This microbial farming demands more ammonium that can be provided internally by the host sponges and some 2.6 million kg of ammonium from the seawater become annually consumed by the aggregations of V. pourtalesii . Such ammonium removal is likely impairing the development of the free-living bacterioplankton and the survival chances of other sponge species that feed on bacterioplankton. Such nutritional competitive exclusion would favor the monospecific character of the V. pourtalesii aggregations. These aggregations also affect the surrounding environment through an annual release of 27.3 million kg of nitrite and, in smaller quantities, of nitrate and phosphate. The complex metabolic integration among the microbiota and the sponge suggests that the holobiont depends critically on the correct functioning of its N-driven microbial engine. The metabolic intertwining is so delicate that it changed after moving the sponges out of their habitat for a few days, a serious warning on the conservation needs of these sponge aggregations.

Microbial diversity of the glass sponge Vazella pourtalesii in response to anthropogenic activities - Kathrin Busch; Lindsay Beazley; Ellen Kenchington; Frederick Whoriskey; Beate M. Slaby; Ute Hentschel (Conservation Genetics, 2020)
Establishment of adequate conservation areas represents a challenging but crucial task in the conservation of genetic diversity and biological variability. Anthropogenic pressures on marine ecosystems and organisms are steadily increasing. Whether and to what extent these pressures influence marine genetic biodiversity is only starting to be revealed. Using 16S rRNA gene amplicon sequencing, we analysed the microbial community structure of 33 individuals of the habitat-forming glass sponge Vazella pourtalesii , as well as reference seawater, sediment, and biofilm samples. We assessed how two anthropogenic impacts, i.e. habitat destruction by trawling and artificial substrate provision (moorings made of composite plastic), correspond with in situ V. pourtalesii microbiome variability. In addition, we evaluated the role of two bottom fishery closures in preserving sponge-associated microbial diversity on the Scotian Shelf, Canada. Our results illustrate that V. pourtalesii sponges collected from protected sites within fishery closures contained distinct and taxonomically largely novel microbial communities. At the trawled site we recorded significant quantitative differences in distinct microbial phyla, such as a reduction in Nitrospinae in the four sponges from this site and the environmental references. Individuals of V. pourtalesii growing on the mooring were significantly enriched in Bacteroidetes, Verrucomicrobia and Cyanobacteria in comparison to sponge individuals growing on the natural seabed. Due to a concomitant enrichment of these taxa in the mooring biofilm, we propose that biofilms on artificial substrates may ‘prime’ sponge-associated microbial communities when small sponges settle on such substrates. These observations likely have relevant management implications when considering the increase of artificial substrates in the marine environment, e.g., marine litter, off-shore wind parks, and petroleum platforms.

Ocean and coastal indicators: understanding and coping with climate change at the land-sea interface - Patricia M. Clay; Jennifer Howard; D. Shallin Busch; Lisa L. Colburn; Amber Himes-Cornell; Steven S. Rumrill; Stephani G. Zador; Roger B. Griffis (Climatic Change, 2020)

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Neurovascular Drug Biotransformation Machinery in Focal Human Epilepsies: Brain CYP3A4 Correlates with Seizure Frequency and Antiepileptic Drug Therapy - Sherice Williams; Mohammed Hossain; Lisa Ferguson; Robyn M. Busch; Nicola Marchi; Jorge Gonzalez-Martinez; Emilio Perucca; Imad M. Najm; Chaitali Ghosh (Molecular Neurobiology, 2019)

Climate‐driven reduction of genetic variation in plant phenology alters soil communities and nutrient pools - Ian M. Ware; Michael E. Van Nuland; Jennifer A. Schweitzer; Zamin Yang; Christopher W. Schadt; Lindsay C. Sidak‐Loftis; Nathan E. Stone; Joseph D. Busch; David M. Wagner; Joseph K. Bailey (Global Change Biology, 2019)
We examined the hypothesis that climate‐driven evolution of plant traits will influence associated soil microbiomes and ecosystem function across the landscape. Using a foundation tree species, Populus angustifolia , observational and common garden approaches, and a base population genetic collection that spans 17 river systems in the western United States, from AZ to MT, we show that (a) as mean annual temperature (MAT) increases, genetic and phenotypic variation for bud break phenology decline; (b) soil microbiomes, soil nitrogen (N), and soil carbon (C) vary in response to MAT and conditioning by trees; and (c) with losses of genetic variation due to warming, population‐level regulation of community and ecosystem functions strengthen. These results demonstrate a relationship between the potential evolutionary response of populations and subsequent shifts in ecosystem function along a large temperature gradient.

The association of children’s mathematic abilities with both adults’ cognitive abilities and intrinsic fronto-parietal networks is altered in preterm-born individuals - J. G. Bäuml; C. Meng; M. Daamen; N. Baumann; B. Busch; P. Bartmann; D. Wolke; H. Boecker; A. Wohlschläger; C. Sorg; Julia Jaekel (Brain Structure and Function, 2017)

Extensive and interrelated subcortical white and gray matter alterations in preterm-born adults - C. Meng; J. G. Bäuml; M. Daamen; J. Jaekel; J. Neitzel; L. Scheef; B. Busch; N. Baumann; H. Boecker; C. Zimmer; P. Bartmann; D. Wolke; et al. (Brain Structure and Function, 2016)

Evaluating markers of epithelial-mesenchymal transition to identify cancer patients at risk for metastatic disease - Evan L. Busch; Temitope O. Keku; David B. Richardson; Stephanie M. Cohen; David A. Eberhard; Christy L. Avery; Robert S. Sandler (Clinical & Experimental Metastasis, 2016)

Atlantic salmon, S almo salar L . are broadly susceptible to isolates representing the N orth A merican genogroups of infectious hematopoietic necrosis virus - G Kurath; J R Winton; O B Dale; M K Purcell; K Falk; R A Busch (Journal of Fish Diseases, 2016)
Beginning in 1992, three epidemic waves of infectious hematopoietic necrosis, often with high mortality, occurred in farmed A tlantic salmon S almo salar L . on the west coast of N orth A merica. We compared the virulence of eleven strains of infectious hematopoietic necrosis virus ( IHNV ), representing the U , M and L genogroups, in experimental challenges of juvenile A tlantic salmon in freshwater. All strains caused mortality and there was wide variation within genogroups: cumulative mortality for five U ‐group strains ranged from 20 to 100%, four M ‐group strains ranged 30‐63% and two L ‐group strains varied from 41 to 81%. Thus, unlike P acific salmonids, there was no apparent correlation of virulence in a particular host species with virus genogroup. The mortality patterns indicated two different phenotypes in terms of kinetics of disease progression and final per cent mortality, with nine strains having moderate virulence and two strains (from the U and L genogroups) having high virulence. These phenotypes were investigated by histopathology and immunohistochemistry to describe the variation in the course of IHNV disease in A tlantic salmon. The results from this study demonstrate that IHNV may become a major threat to farmed A tlantic salmon in other regions of the world where the virus has been, or may be, introduced.

Opportunities and Challenges in the Design and Analysis of Biomass Supply Chains - Pasi T. Lautala; Michael R. Hilliard; Erin Webb; Ingrid Busch; J. Richard Hess; Mohammad S. Roni; Jorge Hilbert; Robert M. Handler; Roger Bittencourt; Amir Valente; Tuuli Laitinen (Environmental Management, 2015)

Implications of p75NTR for dentate gyrus morphology and hippocampus-related behavior revisited - M. Dokter; R. Busch; R. Poser; M. A. Vogt; V. von Bohlen und Halbach; P. Gass; K. Unsicker; O. von Bohlen und Halbach (Brain Structure and Function, 2015)

Method Transfer, Partial Validation, and Cross Validation: Recommendations for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - R. J. Briggs; R. Nicholson; F. Vazvaei; J. Busch; M. Mabuchi; K. S. Mahesh; M. Brudny-Kloeppel; N. Weng; P. A. R. Galvinas; P. Duchene; Pei Hu; R. W. Abbott (The AAPS Journal, 2014)

Estimating Effects of Tidal Power Projects and Climate Change on Threatened and Endangered Marine Species and Their Food Web - D. SHALLIN BUSCH; CORREIGH M. GREENE; THOMAS P. GOOD (Conservation Biology, 2013)
Marine hydrokinetic power projects will operate as marine environments change in response to increased atmospheric carbon dioxide concentrations. We considered how tidal power development and stressors resulting from climate change may affect Puget Sound species listed under the U.S. Endangered Species Act (ESA) and their food web. We used risk tables to assess the singular and combined effects of tidal power development and climate change. Tidal power development and climate change posed risks to ESA‐listed species, and risk increased with incorporation of the effects of these stressors on predators and prey of ESA‐listed species. In contrast, results of a model of strikes on ESA‐listed species from turbine blades suggested that few ESA‐listed species are likely to be killed by a commercial‐scale tidal turbine array. We applied scenarios to a food web model of Puget Sound to explore the effects of tidal power and climate change on ESA‐listed species using more quantitative analytical techniques. To simulate development of tidal power, we applied results of the blade strike model. To simulate environmental changes over the next 50 years, we applied scenarios of change in primary production, plankton community structure, dissolved oxygen, ocean acidification, and freshwater flooding events. No effects of tidal power development on ESA‐listed species were detected from the food web model output, but the effects of climate change on them and other members of the food web were large. Our analyses exemplify how natural resource managers might assess environmental effects of marine technologies in ways that explicitly incorporate climate change and consider multiple ESA‐listed species in the context of their ecological community. Estimación de los Efectos de Proyectos de Energía de las Mareas y el Cambio Climático sobre Especies Marinas Amenazadas y en Peligro y su Red Alimentaria

Maternal coding variants in complement receptor 1 and spontaneous idiopathic preterm birth - Jude J. McElroy; Courtney E. Gutman; Christian M. Shaffer; Tamara D. Busch; Hilkka Puttonen; Kari Teramo; Jeffrey C. Murray; Mikko Hallman; Louis J. Muglia (Human Genetics, 2013)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

A selective combined classification algorithm for mapping alterations on ASTER data - Majid M. Oskouei; Wolfgang Busch (Applied Geomatics, 2012)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Die Untersuchung und Beurteilung von Speiseeis - M. Busch (Journal of Consumer Protection and Food Safety, 2009)

Characterization of expressed class II MHC sequences in the banner-tailed kangaroo rat (Dipodomys spectabilis) reveals multiple DRB loci - Joseph D. Busch; Peter M. Waser; J. Andrew DeWoody (Immunogenetics, 2008)

Dynamics of well-folded and natively disordered proteins in solution: a time-of-flight neutron scattering study - A. M. Gaspar; M.-S. Appavou; S. Busch; T. Unruh; W. Doster (European Biophysics Journal, 2008)

Recent demographic bottlenecks are not accompanied by a genetic signature in banner‐tailed kangaroo rats ( Dipodomys spectabilis ) - JOSEPH D. BUSCH; PETER M. WASER; J. ANDREW DeWOODY (Molecular Ecology, 2007)
Single‐sample methods of bottleneck detection are now routine analyses in studies of wild populations and conservation genetics. Three common approaches to bottleneck detection are the heterozygosity excess, mode‐shift, and M‐ ratio tests. Empirical groundtruthing of these methods is difficult, but their performances are critical for the accurate reconstruction of population demography. We use two banner‐tailed kangaroo rat ( Dipodomys spectabilis ) populations from southeastern Arizona (USA) that are known to have experienced recent demographic reductions to search for genetic bottleneck signals with eight microsatellite loci. Over eight total sample‐years, neither population showed a genetic bottleneck signature. M ‐ratios in both populations were large, stable, and never fell below a critical significance value ( M c ). The mode shift test did not detect any distortion of allele frequencies, and tests of heterozygosity excess were not significant in postbottleneck samples when we used standard microsatellite mutation models. The genetic effects of bottlenecks like those experienced by our study populations should be strongly influenced by rates of mutation and migration. We used genetic parentage data to estimate a relatively high mutation rate in D. spectabilis (0.0081 mutants/generation/locus), but mutation alone is unlikely to explain the temporal distribution of rare alleles that we observed. Migration (gene flow) is a more likely explanation, despite prior mark–recapture analysis that estimated very low rates of interpopulation dispersal. We interpret our kangaroo rat data in light of the broader literature and conclude that in natural populations connected by dispersal, demographic bottlenecks may prove difficult to detect using molecular genetic data.

Real-time-PCR-System zum Nachweis von Bacillus cereus (emetischer Typ) in Lebensmitteln - U. Messelhäusser; M. Fricker; M. Ehling-Schulz; H. Ziegler; D. Elmer-Englhard; W. Kleih; U. Busch (Journal of Consumer Protection and Food Safety, 2007)

“Technically Unavoidable” in Terms of Genetically Modified Organisms – an Approach for Food Control - H.-U. Waiblinger; N. Graf; D. Mäde; K. Woll; U. Busch; B. Holland; H. Pilsl; G. Naeumann; R. Reiting; B. Ehrentreich; M. Schulze; B. Tschirdewahn; et al. (Journal of Consumer Protection and Food Safety, 2007)

Aktueller ZEBS Warencode für Feinkosterzeugnisse - M. Busch (Journal of Consumer Protection and Food Safety, 2006)

Anwendbarkeit der BgVV-Empfehlung zum Nachweis und zur Bewertung von Listeria monocytogenes in Lebensmitteln im Rahmen der Amtlichen Lebensmittelüberwachung - M. Busch (Journal of Consumer Protection and Food Safety, 2006)

The Use of Poly(Sodium N-Undecanoyl-l-Leucylvalinate), Poly(Sodium N-Undecanoyl-l-Leucinate) and Poly(Sodium N-Undecanoyl-l-Valinate) Surfactants as Chiral Selectors for Determination of Enantiomeric Composition of Samples by Multivariate Regression Modeling of Fluorescence Spectral Data - Sayo O. Fakayode; Alicia A. Williams; Marianna A. Busch; Kenneth W. Busch; Isiah M. Warner (Journal of Fluorescence, 2006)

Phosphate uptake by seston and epilithon in the Grand River, southern Ontario - Lisa Barlow-Busch; Helen M. Baulch; William D. Taylor (Aquatic Sciences, 2006)

Parentage analysis detects cryptic precapture dispersal in a philopatric rodent - PETER M. WASER; JOSEPH D. BUSCH; CORY R. McCORMICK; J. ANDREW DEWOODY (Molecular Ecology, 2006)
Locating birthplaces using genetic parentage determination can increase the precision and accuracy with which animal dispersal patterns are established. We re‐analyse patterns of movement away from the birthplace as a function of time, sex and population density for a sample of 303 banner‐tailed kangaroo rats, Dipodomys spectabilis. We located birth sites using a combination of likelihood‐based parentage analysis with live‐trapping of mothers during the breeding season. The results demonstrate that natal‐breeding site distances are density dependent in this species; in particular, both sexes emigrate earlier in the year, and females disperse farther than males, at low population densities. Banner‐tailed kangaroo rats were chosen as a study system because live‐trapping easily detects maternal and offspring locations; nevertheless, parentage analysis reveals that some offspring evade early detection and move substantial distances before their first capture. In a few cases, the approach even detects dispersal out of the natal ‘deme’ prior to first capture. Parentage analysis confirms the extreme philopatry of both sexes but indicates that prior estimates of median dispersal distance were too low. For D. spectabilis , more accurate location of individual birthplaces clarifies patterns of sex bias and density dependence in dispersal, and may resolve apparent discrepancies between direct and indirect estimates of dispersal distance. For species in which mothers can be more reliably trapped than juveniles, using offspring genotypes to locate parents is a novel way that genetic techniques can contribute to the analysis of animal dispersal.

Effects of the atrial antiarrhythmic drug AVE0118 on cardiac ion channels - Heinz Ggelein; J. Brendel; K. Steinmeyer; C. Strbing; N. Picard; D. Rampe; K. Kopp; A.E. Busch; M. Bleich (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Epidemiology of rubella infections in Austria: important lessons to be learned - B. Falkensammer; G. Walder; D. Busch; A. Gieauf; M. Dierich; R. Wrzner (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Inhibitors of ATP-sensitive potassium channels in guinea pig isolated ischemic hearts - A. Weyermann; H. Vollert; A. E. Busch; M. Bleich; H. Ggelein (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Granulocyte colony-stimulating factor (G-CSF) reduces not only gram-negative but also gram-positive infection-associated proinflammatory cytokine release by interaction between Kupffer cells and leukocytes - G. A. Wanner; C. J. Busch; B. Vollmar; M. D. Menger (Inflammation Research, 2004)

Interaction between electron transport at the plasma membrane and nitrate uptake by maize (Zea mays L.) roots - D. Steffen; O. Dring; M. A. Busch; M. Bttger; S. Lthje (Protoplasma, 2001)

MHC class I restricted T cell responses tolisteria monocytogenes, an intracellular bacterial pathogen - Alyce Finelli; Kristen M. Kerksiek; S. Elise Allen; Natalia Marshall; Roberto Mercado; Ingrid Pilip; Dirk H. Busch; Eric G. Pamer (Immunologic Research, 1999)

Effect of extracellular pH on the myo -inositol transporter SMIT expressed in Xenopus oocytes - J. Matskevitch; C. A. Wagner; T. Risler; H. M. Kwon; J. S. Handler; S. Waldegger; A. E. Busch; F. Lang (Pflügers Archiv - European Journal of Physiology, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

K V LQT channels are inhibited by the K + channel blocker 293B - M. Bleich; M. Briel; A. E. Busch; H. J. Lang; U. Gerlach; H. Gögelein; R. Greger; K. Kunzelmann (Pflügers Archiv - European Journal of Physiology, 1997)

Net proton secretion as a parameter for nitrate uptake - M. A. Busch; M. Bttger (Protoplasma, 1997)

Control of food influx by temporal subcastes in the fire ant, Solenopsis invicta - A. Ann Sorensen; Tana M. Busch; S. Bradleigh Vinson (Behavioral Ecology and Sociobiology, 1985)